Zofenopril antitumor activity in mice bearing Ehrlich solid carcinoma: Modulation of PI3K/AKT signaling pathway - Suzan Mohamed Mansour; Rasha Youssef Mohammed Ibrahim (Universidade de São Paulo, 2022)
Abstract Angiotensin-II (AgII) is thought to be crucial for tumor growth and progression. Moreover, hydrogen sulfide (H2S) performs a controversial action in cancer pathology. Zofenopril (ZF) is an angiotensin-converting enzyme (ACE) inhibitor with H2S donating properties. Hence, this study aims at investigating the tumor suppressor activity of ZF and elucidating the involved trajectories in Ehrlich's solid tumor (EST)-bearing mice. EST was induced by the intradermal injection of Ehrlich's ascites carcinoma cells into femoral region. All parameters were assessed after 28 days post-inoculation or one-week thereafter. ZF treatment resulted in significant reduction of tumor weights with marked decrease in IL-6 and VEGF levels in serum, and tumor Ag II and CEA contents. Additionally, the administration of ZF downregulated the tumor gene expression of cyclin-D, ACE-1, and Bcl2 and upregulated the proapoptotic gene, BAX. Moreover, ZF increased CBS gene expression, which is a major contributor to cellular H2S production. In addition, ZF was able to reduce the protein expression of PI3K, pAKT, pGSK-3β, and NFκB. Our study has provided novel insights into the possible mechanisms by which ZF may produce its tumor defeating properties. These intersecting trajectories involve the interference between PI3K/Akt and CBS signaling pathways.